2009
DOI: 10.1007/s12134-009-0108-x
|View full text |Cite
|
Sign up to set email alerts
|

Unequal Before the Law: Immigrant and Racial Minority Perceptions of the Canadian Criminal Justice System

Abstract: This paper examines attitudes towards the criminal justice system among a large, diverse sample of residents from Toronto, Canada. The results indicate that while most residents positively evaluate the performance of the police and criminal courts, black and Chinese Canadians have less favorable views than whites. Compared to whites, racial minority respondents are also much more likely to perceive various forms of discrimination within the justice system. Perceptions of racial bias are particularly widespread… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
73
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 31 publications
6
73
0
Order By: Relevance
“…For example, a study in Toronto found that direct contact with police increased negative evaluations of police treatment of visible minorities (Chow, 2002). Among a general sample of White, Black, and Chinese Canadians, ever arrested by police, number of times stopped by police, and vicarious contact through family and friends were all associated with stronger perceptions of police bias (Wortley & Owusu-Bempah, 2009). Furthermore, communication barriers between police and immigrants, which may include or go beyond language problems, undermine public satisfaction with police.…”
Section: Chinese Immigrants' Perceptions Of Police Biasmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, a study in Toronto found that direct contact with police increased negative evaluations of police treatment of visible minorities (Chow, 2002). Among a general sample of White, Black, and Chinese Canadians, ever arrested by police, number of times stopped by police, and vicarious contact through family and friends were all associated with stronger perceptions of police bias (Wortley & Owusu-Bempah, 2009). Furthermore, communication barriers between police and immigrants, which may include or go beyond language problems, undermine public satisfaction with police.…”
Section: Chinese Immigrants' Perceptions Of Police Biasmentioning
confidence: 99%
“…In terms of immigrant-specific factors, length of time in Canada has been investigated in two studies, generating opposite results. Wortley and Owusu-Bempah (2009) found that perceptions of police bias increased significantly with the length of time an immigrant lived in Canada. In contrast, Chu and Song (2008) found that the longer Chinese immigrants resided in Canada, the less likely they were to perceive police prejudice, suggesting the possibility of curvilinear effects of length of stay on immigrants' perceptions.…”
Section: Chinese Immigrants' Perceptions Of Police Biasmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies conducted in Canada compare Black, White and Chinese Canadians in their perceptions of the police in Toronto area. They find that Chinese are more likely than Whites, but less likely than Blacks, to perceive police bias and discrimination (Wortley 1996, Wortley andOwusu-Bempah 2009).…”
Section: Race/ethnicity and Perceptions Of Police Hispanic And Asian mentioning
confidence: 99%